Halide exchange studies of novel Pd() NNN-pincer complexes - Kuyuldar, Seher; Burda, Clemens; Connick, William B (RSC advances, 2019)
Palladium( ii ) complexes with an NNN type pincer ligand (pip 2 NNN = 2,6-bis(piperdyl-methyl)pyridine) are synthesized and characterized. Electronic and 1 H NMR spectra point to decreasing filled/filled repulsions between the d(Pd) orbitals and the halide lone pair orbitals along the Cl < Br < I series. For all complexes, the most downfield -piperidyl resonance of the pip 2 NNN ligand is sensitive to changes in the coordinated halide while the meta -pyridyl and benzylic resonances are sensitive to changes in the counter anion. This sensitivity is utilized to study halide association and exchange at the fourth coordination site. Conductivity and 1 H NMR spectroscopy confirm the interaction between the exogenous anion (Cl , Br , BF 4 ) and Pd(pip 2 NNN)X + (X = Cl, Br). Halide exchange in palladium( ii ) complexes with NNN-type pincer ligands is investigated.